2013
DOI: 10.3390/ijms14034613
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immobilization of Bacillus licheniformis γ-Glutamyl Transpeptidase on Aldehyde-Functionalized Magnetic Nanoparticles

Abstract: This work presents the synthesis and use of surface-modified iron oxide nanoparticles for the covalent immobilization of Bacillus licheniformis γ-glutamyl transpeptidase (BlGGT). Magnetic nanoparticles were prepared by an alkaline solution of divalent and trivalent iron ions, and they were subsequently treated with 3-aminopropyltriethoxysilane (APES) to obtain the aminosilane-coated nanoparticles. The functional group on the particle surface and the amino group of BlGGT was then cross-linked using glutaraldehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…With respect to γ-PGA production, overexpression of the pgdS gene in B. licheniformis WX-02 unexpectedly increased the γ-PGA production by 54% and decreased the molecular masses of γ-PGA molecules (Tian et al 2014). GGT of B. licheniformis strain has been well characterized in heterogeneous expression systems (Lin et al 2006) and has been applied in enzymatic reactions (Chen et al 2013). However, the effects of ggt overexpression or disruption on γ-PGA production of B. licheniformis have not been described previously.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to γ-PGA production, overexpression of the pgdS gene in B. licheniformis WX-02 unexpectedly increased the γ-PGA production by 54% and decreased the molecular masses of γ-PGA molecules (Tian et al 2014). GGT of B. licheniformis strain has been well characterized in heterogeneous expression systems (Lin et al 2006) and has been applied in enzymatic reactions (Chen et al 2013). However, the effects of ggt overexpression or disruption on γ-PGA production of B. licheniformis have not been described previously.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study conducted on immobilized lipase by various MNPs (naked and modified Fe 3 O 4 ) demonstrated that the amount of immobilized lipase increased with increasing enzyme concentration, but the activity of immobilized enzyme was found reduced at the same condition (31). It probably due to the multiple layers of enzyme molecules were formed on the surface of MNPs at high enzyme loading, which might block the active sites of the enzyme and caused the diffusion limitation of the substrate (32).…”
Section: Conditions Of Faes Immobilization On the Mnpsmentioning
confidence: 86%
“…Currently, immobilization of an enzyme is one of the widely performed methods. GGTs from Bacillus species have also been immobilized [40][41][42] , but the authors provide data of the total enzymatic activity, which implies both transpeptidation and hydrolysis activities. Unlike E. coli GGT, GGTs from Bacillus species have pH optima of both activities at basic pH.…”
Section: Future Perspectivementioning
confidence: 99%